Evaluasi Risiko Kualitas Jamur Menggunakan Metode FMEA - Rizqi, A Faisal Maulana; Kurniawan, Rudi; Riyana, Iis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Risk management at CV Budidaya Jamur Sejati is very important to avoid defects in mushroom cultivation caused by failures in the cultivation system. Risk analysis is also important to avoid failures that may occur in the oyster mushroom cultivation system. In this study, the integrated FMEA method was used to analyze the oyster mushroom cultivation process at CV Budidaya Jamur Sejati During the period from December to January 2025, CV Budidaya Jamur Sejati experienced cultivation failure at the maintenance stage, producing 5kg to 7kg of mushrooms. CV Budidaya Jamur Sejati does not yet know the types of risks faced in the mushroom maintenance process. FMEA is applied to the mushroom process to identify the main failure risks and sort all risks related to potential cultivation failures. There are 7 root causes of failure identified in the cultivation process. The results obtained from the application of the FMEA method indicate that this information can be used as a preventive and corrective step to minimize the failure of the mushroom cultivation process.